2002
DOI: 10.21273/jashs.127.5.742
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Effects of Mycorrhizal Inoculation and Organic Soil Amendments on Nitrogen Acquisition and Growth of Highbush Blueberry

Abstract: The ability of mycorrhizal and nonmycorrhizal `Elliott' highbush blueberry (Vaccinium corymbosum L.) plants to acquire soil N under different preplant organic soil amendment regimes (forest litter, rotted sawdust, or no amendment) was investigated in a field experiment using 15N labeled (NH4)2SO4. Plants inoculated with an ericoid mycorrhizal isolate, Oidiodendron maius Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 25 publications
0
13
1
1
Order By: Relevance
“…These higher concentrations are a result of the EMF enhancing uptake of inorganic N and P (Mitchell and Read, 1981;Stribley and Read, 1976) and organic or insoluble N and P compounds from the soil (Kerley and Read, 1995;Read et al, 1989;Stribley and Read, 1980). A study using 15 N-labeled ammonium in fumigated soil found that blueberry plants inoculated with ericoid mycorrhizal fungi had lower 15 N enrichment (Yang et al, 2002). This indicated that in mycorrhizal blueberry plants the 15 N label was diluted by uptake of alternative N sources.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These higher concentrations are a result of the EMF enhancing uptake of inorganic N and P (Mitchell and Read, 1981;Stribley and Read, 1976) and organic or insoluble N and P compounds from the soil (Kerley and Read, 1995;Read et al, 1989;Stribley and Read, 1980). A study using 15 N-labeled ammonium in fumigated soil found that blueberry plants inoculated with ericoid mycorrhizal fungi had lower 15 N enrichment (Yang et al, 2002). This indicated that in mycorrhizal blueberry plants the 15 N label was diluted by uptake of alternative N sources.…”
Section: Discussionmentioning
confidence: 99%
“…These higher concentrations are a result of the fungus not only enhancing uptake of soluble inorganic N and P (Mitchell and Read, 1981;Stribley and Read, 1976) but also utilizing organic or insoluble N and P compounds in the soil (Kerley and Read, 1995;Read et al, 1989;Stribley and Read, 1980). When 15 N labeled ammonium is fed to mycorrhizal and non-mycorrhizal Vaccinium growing in sterile and fumigated soil, mycorrhizal plants have significantly greater yields and total nitrogen content than nonmycorrhizal plants; however mycorrhizal plants have lower 15 N enrichment (Stribley and Read, 1974a;Yang et al, 2002), indicating that the label is diluted by alternative N sources in mycorrhizal plants. In addition to an ability to readily use ammonium and nitrate, EMF can also use amino acids, peptides, proteins, and polymers such as chitin and lignin to transfer substantial quantities of N to the plant host (Bajwa and Read, 1985;Bajwa and Read 1985;Kerley and Read, 1995;Kerley and Read, 1997;Kerley and Read, 1998;Stribley and Read, 1980).…”
Section: International Journal Of Fruit Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Colonization of blueberry can vary significantly with cultivar (Czesnik and Eynard, 1990;Eynard and Czesnik, 1989), rate of fertilizer application (Powell, 1982) and the amount and type of soil organic matter present in the soil (Blasing, 1989;Czesnik and Eynard, 1990;Eynard and Czesnik, 1989;Haynes and Swift, 1985;Yang et al, 2002). A field study in Northeastern North America found that inoculation of tissue-cultured highbush blueberry increased plant growth and root dry weight (Yang et al, 2002). However, increased application of fertilizers can depress mycorrhizal infection levels in blueberry seedlings (Powell, 1982;Golldack et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Cultivar (i.e., genotypes) specific effects of inoculation were found by others as well (Scagel, ; Scagel and Yang, ). Early‐blooming cultivars tended to have higher levels of colonization than later‐blooming ones (Scagel and Yang, ) and colonization altered the ways in which plants utilize nutrients (Powell and Bates, ; Yang et al., ; Scagel, ; Zinati et al., ). Even closely related genotypes showed a high degree of variability in response to inoculation.…”
Section: Discussionmentioning
confidence: 99%